(untitled) (Journal of Medicine, 2020)
Hypokalemia is a common clinical problem in endocrinologists’ and nephrologists’ practice. There are many obvious causes of hypokalemia such as diarrhea, vomiting or diuretics abuse. Other causes such as tubulopathies are rarely observed and their diagnosis is more challenging. There are many inherited and acquired tubulopathies causing hypokalemia, sometimes severe and life-threatening. We report a case of a middle aged female patient who presented with weakness of upper and lower limbs, muscle pain and oliguria. On evaluation, she had hypokalemia, hypomagnesemia, metabolic alkalosis and hypocalciuria and diagnosis of Gitelman syndrome was established. In addition, she had acute kidney injury (AKI ) due to rhabdomyolysis secondary to hypokalemia. A short review on the etiology, pathogenesis and management of Gitelman syndrome is presented. J MEDICINE JUL 2020; 21 (2) : 105-108